Increasing Efficiency of Repetitive Electroacupuncture on Purine- and Acid-Induced Pain During a Three-Week Treatment Schedule - Li, Jie; Zhang, Ying; Illes, Peter; Tang, Yong; Rubini, Patrizia (Frontiers in Pharmacology, 2021)
Acupuncture (AP) is an important constituent of the therapeutic repertoire of Traditional Chinese Medicine and has been widely used to alleviate chronic painful conditions all over the world. We studied in rats the efficiency of electroacupuncture (EAP) applied to the Zusanli acupoint (ST36) as an analgesic treatment over a 3 week’s period of time on purine- (α,β-methylene ATP, dibenzoyl-ATP) and acid- (pH 6.0 medium) induced pain in the rat paw. The two ATP-derivatives stimulated P2X3 and P2X7 receptors, respectively, while the slightly acidic medium stimulated the “acid-sensitive ion channel 3” (ASIC3). It was found that the P2X7 receptor and ASIC-mediated pain was counteracted by EAP with greater efficiency at the end than at the beginning of the treatment schedule, while the P2X3 receptor-mediated pain was not. Our finding has important clinical consequences, especially because it appears to disagree with the assumption that AP is due to the release of peripheral and central opioid peptides causing the well-known tolerance to their effects. In consequence, AP is a convenient therapeutic instrument to treat subacute and chronic pain.